2017
DOI: 10.1021/acs.energyfuels.6b02902
|View full text |Cite
|
Sign up to set email alerts
|

Tribological Approach to Investigate the Interface Properties in Metallurgical Coke

Abstract: Metallurgical coke is a brittle composite material comprising predominantly carbon derived from both reactive and inertinite coal macerals. During cokemaking, these macerals form the porous coke matrix. The interfaces between the distinct maceral derived components, known as textures in the final coke structure, are well-known to be a major source of weakness in some metallurgical cokes. In this paper, we present a novel approach which applies techniques used in tribology to investigate the strength of the int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 13 publications
0
13
0
Order By: Relevance
“…For the latter point, it was important that distinct differences in the width and depth of the tracks between cokes formed from coals with different properties were easily observed. The testing conditions differed from our previous publication as we were limited by the maximum loading capacity of the load cell available for those tests; therefore, the conditions for the earlier tests were not optimal. All experiments were performed at room temperature and in the absence of added lubricant.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…For the latter point, it was important that distinct differences in the width and depth of the tracks between cokes formed from coals with different properties were easily observed. The testing conditions differed from our previous publication as we were limited by the maximum loading capacity of the load cell available for those tests; therefore, the conditions for the earlier tests were not optimal. All experiments were performed at room temperature and in the absence of added lubricant.…”
Section: Methodsmentioning
confidence: 99%
“…The tribological wear and fracture mechanisms are linked to the different carbon forms in a coke. There are three main wear mechanisms relevant to the analysis of coke cold strength that have been observed during tribological testing of coke: adhesive wear is the transfer of material from the coke surface to the indenter; delamination wear refers to the subsurface cracks parallel to the surface; abrasive wear is a “scratching” and microcracking of the softer coke surface by the indenter. Abrasive wear becomes increasingly dominant as the tribological test progresses, as the ejected coke particles are transferred to the indenter and track surface and act as abrasion particles, causing further damage to the coke bulk surface.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The probability that a calculated high stress point will break is dependent not only on the microstructure but also on the physical properties of the textural constituents at that point. For example, our previous fractographic [13] and tribological [25] analysis of various cokes of single coal origin has indicated that the properties of the inerts within a single coke show varying interaction strength with the RMDC. Fig.…”
Section: Finite Element Analysismentioning
confidence: 99%
“…Furthermore, volumetric destruction of coke, wear, and deformation due to solution loss make it difficult to predict in-furnace phenomena. 12) A "holistic" operation design based on a phenomenological understanding of the melt dripping in heterogeneous coke beds is strongly desired.…”
Section: Introductionmentioning
confidence: 99%